The role of audience design and goal bias in message generation: Evidence from Chinese source-goal motion events - Chen Zhao; Rui Xu; Tingting Sun (Language and Cognition)
This study investigated the effects of audience design and goal bias in Chinese speakers’ message generation of source-goal motion events (e.g., A bird flies from the tree to the house), using picture description and memory tasks. The status of the source (e.g., the tree) or the goal (e.g., the house) was manipulated as known or unknown to the confederate addressees. The findings revealed that the participants were more likely to omit the sources when they were mutually known to the addressee than when they were not. However, participants showed similar accuracy in detecting source changes, regardless of whether the sources were known to the addressee. Moreover, they consistently mentioned goals and showed similar accuracy in detecting goal changes, regardless of whether the goals were known or unknown to the addressee. The results suggest that audience design influenced the speakers’ mention of sources, but not their memory of them. It did not affect either the mention or the memory of goals. Goal bias was not consistently observed across the two experiments, both linguistically and in memory. This suggests a fragile goal bias in Chinese. Taken together, these findings demonstrate that audience design and goal bias influence the message generation of motion events in Chinese speakers.